Pengembangan Bahan Ajar Penyajian Data Berbasis Lectora Inspire dengan Pendekatan CTL di Kelas IV - Riri Zulvira; Yetti Ariani (Universitas Negeri Padang, 2020)
This research aims to develop data presentation teaching material that based on Lectora Inspire with CTL approach in class IV 15 Elementary School Ulu Gadut with interactive CD form which is valid and practical to use the 4-D development model of Thiagarajan. The stages are define, design, development, and dissemination. The subjects of this study were 3 expert, 1 class IV teacher and 20 students in grade IV-A Elementary School 15 Ulu Gadut. The instrument used is an expert validation sheet, teacher and students response questionnaire. Products research results: (1) data presentation teaching material that based on Lectora Inspire with CTL approach in class IV declared to be valid for use by material expert, linguists and media expert with excellent category with an overall assessment of the 95,67 validator, (2) teacher and student responses to the data presentation teaching material that based on Lectora Inspire with CTL approach in class IV elementary school obtain a very practical category with an average value of 92,72 % and 94,54 %.